E-TAILING: NATURE AND CHARACTERISTICS - Тягунова, Н. М.; Гудзенко, М. Ю. (Scientific Progress & Innovations, 2013)
The article summarized and systematized approaches of domestic and foreign scientists to determine the nature of the concepts of “E-commerce” and “Internet-commerce”. The authors give a definition of “E-tailing” based on the analysis of the main components of trading activities undertaken by telecommunication capabilities of the Internet: E-tailing is a form of trade, at which all activity of selling or buying, is provided by the Internet. Thus internal processes, related to organization of trading activity, can be realized by different electronic methods.